Two-photon photodynamic therapy and its potential application to age related macular degeneration - Karotki, A; Khurana, M; Bisland, S; Moriyama, E; Simpson, E; Campbell, M; Collins, H; Anderson, H; Cramb, D; Wilson, B (2007)
Photodynamic therapy (PDT) using verteporfin is widely used for treatment of age related macular degeneration (AMD). Due to non-perfect selectivity of the drug accumulation in the neovasculature some collateral damage to healthy tissue arises during the treatment. Damage to healthy structures in the eye is always a concern because of a high probability of reducing visual acuity. Two-photon (2-γ) photodynamic therapy potentially offers much higher treatment selectivity than its one-photon (1-γ) counterpart. By utilizing focused light for 2-γ excitation, treatment volumes on the order of microliters can be achieved thus maximizing localized insult to abnormal blood vessels and sparing healthy tissue. We propose that 2-γ photodynamic therapy will be valuable in the treatment of choroidal neovascularization secondary to age related macular degeneration as well as other conditions. To ascertain feasibility of 2-γ photodynamic therapy we measured 2-γ spectrum and cross sections of verteporfin (80 GM at 940 nm, 1 GM = 10 -50 cm4s/photon), chlorin e6 (14 GM at 800 nm) and tetrasulfonated aluminum phthalocyanine (140 GM at 900 nm) and investigated their in vitro efficiency under 2-γ excitation. Only verteporfin demonstrated cell kill under the used irradiation parameters (average light intensity 9.1 mW, wavelength 850 nm, total light dose 6900 J/cm2). Dorsal skinfold window chamber model in mouse was used to test efficiency of 2-γ PDT with verteporfin in vivo. Although we were able to induce photodynamic damage to a blood vessel using 1-γ excitation, 2-γ excitation resulted in no visible damage to irradiated blood vessel. The most probable reason is low efficiency of verteporfin as a 2-γ photosensitizer. We also report 2-γ spectrum of new photosensitizer, HCC4 (4300 GM at 830 nm), specifically designed for efficient 2-γ excitation.